Lived Experiences of Physiotherapists in Caring for People with Advanced Amyotrophic Lateral Sclerosis in Portugal: A Phenomenological Study - Andreia Monteiro; Amira Mohammed Ali; Carlos Laranjeira (Behavioral Sciences)
Amyotrophic lateral sclerosis (ALS) is a disease that has a multidimensional impact on a person’s life, with symptoms associated with a significant loss of autonomy. Specialized palliative care (PC) should be provided early and throughout the course of the disease. Indeed, physiotherapists should be understood as integral members of the multidisciplinary team in PC, in the care and improvement of the quality of life of these people. This study aimed to describe the lived experience of physiotherapists in the context of intervention in people with advanced ALS and their families. Descriptive phenomenology was employed as a framework for conducting semi-structured interviews to reveal experiences. Sixteen physiotherapists who performed interventions on at least one person with advanced ALS in the last 2 years were included in the study. The study involved conducting semi-structured individual interviews, through the Zoom® videoconferencing platform (version 6.4.3). Data were analyzed according to Giorgi’s five-stage approach and managed using webQDA software (Version 3.0, University of Aveiro, Aveiro, Portugal). The COREQ checklist was applied in the study. Participants were mostly female (n = 12) and aged between 26 and 55 years (M = 36.81; SD = 6.75). Four constituents were identified: (1) undulating course of a complex disease; (2) barriers to person-centered care; (3) enablers of person-centered care; (4) transition between curative and palliative care. The findings illustrate the multidimensional impact of the disease trajectory on the person and their family. This study highlights the need to invest in specialized training for physiotherapists, contributing to a person-centered PC practice with an impact on promoting comfort and quality of life.